Detection of autophagy in Hirschsprung's disease: implication for its role in aganglionosis. Issue 17 (2nd December 2015) - Huang, Qiang; Ge, Xin; Li, Peng; Duan, Yitao; Guo, Zhengtuan; Zheng, Baijun; Wu, Xuanlin; Guo, Xinkui; Gao, Ya
Abstract : Hirschsprung's disease (HD) is a common congenital gastrointestinal malformation, characterized by the lack of ganglion cells from the distal rectum to the proximal bowel, but the pathogenesis is not well understood. This paper evaluates the effects of autophagy in HD. Using electron microscopy, the autophagosomes were detected in three segments: narrow segment (NS), transitional segment (TS), and dilated segment (DS). Typical autophagosome structures are found in the Auerbach plexus of both NS and TS. Real-time PCR results showed that Beclin1 (NS vs. TS, P <0.01) and LC3 (NS vs. TS, P <0.05) mRNA were the highest in the NS, but p75 (NS vs. TS, P <0.01) was the highest in the DS. Correlation analysis results showed a positive correlation between Beclin1 and LC3 mRNA levels ( R =0.736, P =0.000), whereas inverse correlations were found between p75 and Beclin1 / LC3 mRNA levels ( p75 vs. Beclin1 : R =−0.714, P =0.000; p75 vs. LC3 : R =−0.619, P =0.000). Immunohistochemistry analyses indicated a consistent result with mRNA levels, by increased Beclin1 -positive and LC3 -positive neurons, but reduced p75 -positive neurons in the Auerbach plexus of TS compared with DS. These findings indicated that autophagy exists in the bowel of patients with HD. On the basis of the detection of the highest expression of the autophagy genes in NS, autophagy may additionally cause the lack of neurons. Abstract : Supplemental Digital Content is available in the text.